Evaluation of resistance in different varieties/genotypes of bottle gourd (Lagenaria siceraria) against Cercospora leaf spot under field conditions - MAHESHWARI, S K; CHOUDHARY, B R; SINGH, D; SHARMA, B D; SHARMA, S K (The Indian Journal of Agricultural Sciences, 2015)
Cultivation of resistant or tolerant cultivars is one of the best options to minimize the losses due to diseases. Seventeen bottle gourd [Lagenaria siceraria (Mol.) Standl.] varieties/genotypes (Pusa Naveen, Pusa Samridhi, Udaipur Local, Pusa Santushti, Pusa Sandesh, PSPL, Chomu Local, Azad Harit, Panchmahal Local, Arka Bahar, Thar Samridhi, PN 22, DBG 5, DBG 6, Jodhpur Local, IC 567538 and Sriganganagar Local) were evaluated for resistance against Cercospora leaf spot during the rainy season of 2011 and 2012 under hot arid field conditions of Rajasthan. Among them, none was found immune or resistant, four varieties (Pusa Naveen, Pusa Santushti, Pusa Samridhi and Pusa Sandesh) were found to be moderately resistant and four (PSPL, Arka Bahar, PN22 and DBG6) were moderately susceptible and the remaining nine were susceptible.